Kajian Elemen Pembentuk Citra Path Koridor Jelekong Kabupaten Bandung - Dinda Farizia; Weishaguna (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. In 2011, the Regent of Bandung Regency designated Kelurahan Jelekong as an arts and culture-based tourism village, driven by painting and wayang, which are the pillars of art and culture in Jelekong. Although arts and culture are thriving in the Jelekong corridor, there is no clear signposting between art venues, which is important in shaping the image of the area. This research aims to explore the image-forming elements of the Jelekong corridor path, using figure ground, outline, semiotic, and descriptive analysis with observation, mental map, mapping, interview, and literature study techniques. The results show that the image-forming elements of the path in the Jelekong corridor consist of buildings, street furniture, and signage. These elements have their own structure and meaning. There are three groups of building functions in the Jelekong cultural arts corridor: trade and services, mixed functions, and residential. Signage most adopts Sundanese culture, while buildings and street furniture need better design to strengthen the image of the Jelekong corridor. Abstrak. Pada tahun 2011, Bupati Kabupaten Bandung menetapkan Kelurahan Jelekong sebagai desa wisata berbasis seni dan budaya, didorong oleh seni lukis dan wayang yang menjadi pilar seni dan budaya di Jelekong. Meskipun seni dan budaya berkembang pesat di koridor Jelekong, belum ada penunjuk arah yang jelas antar tempat kesenian, yang penting dalam membentuk citra wilayah. Penelitian ini bertujuan mengeksplorasi elemen pembentuk citra path koridor Jelekong, menggunakan analisis figure ground, outline, semiotik, dan deskriptif dengan teknik observasi, mental map, pemetaan, wawancara, dan studi pustaka. Hasilnya menunjukkan elemen pembentuk citra path di koridor Jelekong terdiri dari bangunan, street furniture, dan signage. Elemen-elemen ini memiliki struktur dan makna tersendiri. Terdapat tiga kelompok fungsi bangunan di koridor seni budaya Jelekong : perdagangan dan jasa, fungsi campuran, dan permukiman. Signage paling mengadopsi budaya Sunda, sedangkan bangunan dan street furniture membutuhkan desain yang lebih baik untuk memperkuat citra koridor Jelekong.